Cell-Cell Coupling And Cell Hubness Make a Cell More Resistant Against Low-Frequency Electromagnetic Stress: A Computational Modeling Study - Farashi, Sajjad (International Journal of Scientific Research in Biological Sciences, 2021)
In this study, a computational framework was used to check out how cell physical connections to neighboring cells and the hubness property of a cell affect its response to environmental stress such as extremely low-frequency electromagnetic (ELF-EMF) intervention. For this purpose, a mathematical model of a special kind of excitable cells, i.e. human pancreatic beta-cell was incorporated. The connection between cell models was also formulated by a mathematical expression. Furthermore, by changing the characteristics of the model toward increasing calcium dynamics, the hubness property was assigned to the cell model. Using this mathematical model the effect of ELF-EMF was investigated. The simulation results indicated that the physical connection of a cell to its neighbor cells enhanced its potential to tolerate ELF-EMF stresses, possibly via channel sharing or via perturbing ELF-EMF field. Also, when a cell possessed the hubness property, it showed higher resistance against ELF-EMF interventions, possibly due to different calcium dynamics compared with non-hub cells.